Conduction Disturbances after the Superior Septal Approach for Mitral Valve Repair - Misawa, Yoshio; Ohki, Shin-ichi; Kaminishi, Yuichiro; Sakano, Yasuhito; Aizawa, Kei; Saito, Tsutomu; Konishi, Hiroaki; Muraoka, Arata (IntechOpen, 2011)
None